2022
DOI: 10.3390/cancers14122946
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Reduced Dose Rate (PRDR) Radiotherapy for Recurrent Primary Central Nervous System Malignancies: Dosimetric and Clinical Results

Abstract: Purpose: The objective was to describe PRDR outcomes and report EQD2 OAR toxicity thresholds. Methods: Eighteen patients with recurrent primary CNS tumors treated with PRDR at a single institution between April 2017 and September 2021 were evaluated. The radiotherapy details, cumulative OAR doses, progression-free survival (PFS), overall survival (OS), and toxicities were collected. Results: The median PRDR dose was 45 Gy (range: 36–59.4 Gy); the median cumulative EQD2 prescription dose was 102.7 Gy (range: 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With a notable median follow-up of 64 months, the estimated 4-year OS and PFS were 60% and 35.7%, respectively. In a recent publication, Kutuk et al [ 13 ] reported on their experience with PLDR re-irradiation in 18 patients with recurrent primary CNS malignancies. At a median follow-up of 8.7 months, the median PFS and OS were 5.7 months and 6.7 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With a notable median follow-up of 64 months, the estimated 4-year OS and PFS were 60% and 35.7%, respectively. In a recent publication, Kutuk et al [ 13 ] reported on their experience with PLDR re-irradiation in 18 patients with recurrent primary CNS malignancies. At a median follow-up of 8.7 months, the median PFS and OS were 5.7 months and 6.7 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous research has shown encouraging results for Re-RT using PRDR-RT in multiple disease sites. [7][8][9] However, there are minimal reports on the use of PRDR-RT for HNSCC. The purpose of this study was to report preliminary efficacy and toxicity data from a single institution of a consecutive cohort of patients with HNSCC who received Re-RT via PRDR-RT.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Photon PRDR is also associated with modest treatment-related toxicities and not widely available. 5 …”
mentioning
confidence: 99%